PERDAGANGAN KARET ALAM ANTARA NEGARA PRODUSEN UTAMA DENGAN AMERIKA SERIKAT - M. SINAGA, BONAR; -, ELWAMENDRI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 1 Februari 2004)
The result of reseach shows that expor supply of the main producer country to the United States has the positive slope and inelactic toward price. Meanwhile the palm plant was competitive plant for rubber plant. While, rubber production has potential to increase the rubber expor of technical spesification. Rasio of Domestic rubber consumption with rubber expor of technical specification each of the main prodicer country has potential to decrease ability rubber expor of tecnical specification. Rubber expor price of technical specification in main producer country in short and long term was not resposive toward change of price in United State country. Impor demand the technical specification rubber United State has the negative slope and inelactic toward price. The sinthetic rubber is substitute the natural rubber and increasing the otomotive industry production and increasing the United State economy capcity tend to increase demand of technical natural rubbber in United State.
Keywords: Supply, Demand, Price dan Natural Rubber